THE BREASTFEEDING EXPERIENCES OF MOTHERS WITH HISTORY OF INFECTED WITH COVID-19: A QUALITATIVE STUDY - Irma Nurbaeti; Nansya Handayani (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Postpartum mothers are the vulnerable population when exposure by the COVID-19. Transmission of the COVID-19 can cause a change in the breastfeeding process and has an impact on the mother's psychology. However, little documented experience of breastfeed of mothers who are infected with COVID-19 in Indonesia. Objectives: The aim of study was to explore the experience of breastfeeding of mothers who have a history of being infected with COVID-19 Methods: A qualitative method with a phenomenological approach was used in this study. A total of 12 postpartum mothers who were history infected with COVID-19. Participants were recuited by purposive sampling. Data collection, in Lebak, Banten Province from April to May 2022, was performed by in-depth interviews, assisted by interview guidelines, recording devices, note-taking equipment, and field notes. The data were analyzed by the Colaizzi method Results: The result of this study are the feelings of breastfeeding mothers when infected with COVID-19 consists of two sub-themes: (1) feelings sadness, (2) feelings fear. The breastfeeding experience of mothers infected with COVID-19 there are 4 sub-themes: (1) how to provide nutrition to babies, (2) the frequency of breastfeeding babies, (3) health protocols carried out by mothers, (4) sources of information related to breastfeeding that mother got. The support person during difficult times obtained several sub-themes: (1) support from husbands, (2) support from parents, (3) support from in-laws (4) support from family, (5) support from friends or relatives, (6) support from neighbors, (7) support from health workers. Conclusion: COVID-19 infection tends to impact to psychological aspect among breastfeeding mothers. Support from significant persons, relative and health workers needed for successful breastfeeding during and after being infected with COVID-19.